Secondary Students’ Career Development Phenomenarratives - Openshaw, Michael James (Curtin University, 2023)
Career education and guidance can support the development of secondary students as they aspire toward their life goals. This research explored the lived experiences of three young people through the creation of phenomenarratives. A narrative co-reflection process was developed as part of the students’ personalised career guidance planning. Findings indicated the importance of career education that supports personalised and holistic learning experiences to develop students’ self-awareness, work skills, networks and confidence in their future direction.